The Role of Teachers in the Learning Process, Internal and External Learning Problems, and Processing of Learning Resources - Wati Irnawati; Wildan Solihin; Johan Jonathan; M Fachri Fachrezi (Penerbit Hellow Pustaka, 2025)
The learning process is the core of education, involving interactions between teachers and students. Teachers play a crucial role as facilitators, motivators, innovators, and evaluators in creating an effective learning environment. However, various challenges may hinder the learning process, both internally and externally. Internal problems include a lack of motivation, difficulties in understanding the material, and psychological factors such as stress and anxiety. Meanwhile, external challenges may arise from a lack of family support, economic limitations, and ineffective teaching methods. Additionally, proper management of learning resources is essential to improving learning quality. The use of technology, the availability of diverse learning resources, and the creation of a conducive learning environment are some strategies that can be applied to support learning success. Therefore, teachers are required to continuously innovate and adapt their teaching strategies to meet students' needs.